Pengaruh Faktor Psikologik, Sosial dan Finansial Terhadap Kepuasan Kerja Karyawan Penyadap Karet di PT. Atjeh Raya Corpindo Kab. Aceh Timur - Andi Akmal; Siti Balqies Indra; Cut Gustiana (Jurnal Penelitian Agrisamudra, 2019)
The aim of this research was to know the effect of psychological, social and financial factors to rubber tappers employees statisfaction in PT. Atjeh Raya Corpindo (ARCO) East Aceh district. This research used case study method. Location was determined purposively in PT. ARCO Kebun Alur Buluh, Birem Bayeun sub-district, East Aceh district. The objects of this research only a rubber tappers with mount of sample 33 person with multiple regression linear. The result showed that psychological dan social factor very effected meanwhile financial factor affected to rubber tappers employees statisfaction in PT. Atjeh Raya Corpindo (ARCO) East Aceh district